When COVID-19 Met Families Living in Armed-Conflict Zones: The Importance of Maternal Trauma and Child Self-Regulation - Levavi, Kinneret; Yakov, Porat; Pike, Alison; Deater-Deckard, Kirby; Hadar, Amnon; Bar, Guy; Froimovici, Miron; Atzaba-Poria, Naama (Frontiers in Psychiatry, 2022)
The COVID-19 outbreak began in Israel at the end of February 2020, and on March 17, 2020, a general lockdown was announced. Families were instructed to stay at home and schools and nonessential businesses were closed. Aiming to understand how families who were already living in areas of high exposure to armed conflict would be affected by another external stressful condition, data were collected before and after the outbreak. Mothers and children (aged 10-45 months) were recruited from areas with high (n = 40) and low (n = 78) exposure to armed conflict. Mothers reported on their posttraumatic stress symptoms (PTSS) and on their child’s effortful control tendencies prior to the outbreak. Toward the end of the first lockdown, mothers were interviewed regarding adverse effects of the outbreak on their family. No group differences were found for maternal perceptions of adverse effects of COVID-19. However, a moderation model was revealed, indicating that maternal PTSS as well as child effortful control predicted adverse effects of COVID-19 only in the high-exposure group. Results are discussed considering cumulative stress and risk factors.